The National American Gini Coefficient and Regional Costs of Living Differences - Buss, J. A. (Journal of Income Distribution®, 1992)
One criticism of the methodology used by the U.S. Census Bureau to estimate the official Gini coefficient is that the underlying income data are not adjusted to account for regional differences in the cost of living. In this study such adjustments are made to the 1970-1987 income data. These adjusted income figures are then incorporated into the Fei-Ranis-Kuo model. The new estimates of the Gini coefficient are not significantly different from those published by the Census Bureau. Thus, the Census Bureau’s failure to take regional costs of living differences into account does not distort the national Gini coefficient.